The Role of Integrated Reporting in Enhaching Firm Value : A Stakeholder Theory Based Analysis - Muhammad Astri Yulidar Abbas (PT. Hafasy Dwi Nawasena, 2026)
Integrated Reporting (IR) has emerged as an innovative corporate reporting framework that integrates financial and non-financial information to demonstrate how organizations create sustainable value over time. In the context of increasing stakeholder demands for transparency and accountability, IR is considered an important mechanism for strengthening corporate legitimacy and enhancing firm value. Grounded in Stakeholder Theory, this study aims to analyze the role of Integrated Reporting in improving firm value through stakeholder-oriented disclosure practices. This research employs a quantitative approach using secondary data obtained from companies’ annual reports, integrated reports, and financial statements of publicly listed firms that implement integrated reporting practices. Data were collected using documentation techniques and analyzed using panel data regression analysis to examine the influence of Integrated Reporting Quality on firm value while controlling for firm size and leverage. The results indicate that Integrated Reporting Quality has a positive and significant effect on firm value as measured by Tobin’s Q. These findings suggest that companies with higher-quality integrated disclosures tend to achieve stronger market valuation due to improved transparency, reduced information asymmetry, and enhanced investor confidence. From the perspective of Stakeholder Theory, integrated reporting strengthens relationships with diverse stakeholders and improves corporate credibility in capital markets. In conclusion, integrated reporting plays a strategic role in enhancing firm value by improving transparency, stakeholder engagement, and long-term value creation.